Formation of Desacetylcephalosporin C in Cephalosporin C Fermentation - Huber, F. M. (1968)
The origin of desacetylcephalosporin C in cephalosporin C fermentation broths was investigated. Esterase activity was detected in cell-free extracts of Cephalosporium acremonium, but these extracts failed to deesterify cephalosporin C. When cephalosporin C was added to sterile and inoculated fermentation media, the antibiotic decayed at nearly identical rates. The formation of desacetylcephalosporin C during the fermentation was measured by quantitative chromatography and by the incorporation of valine-1-(14)C into the molecule. The rate constants obtained from the results of these experiments were equivalent to those for the decay of cephalosporin C in sterile and inoculated media. The data demonstrate that desacetylcephalosporin C is produced by nonenzymatic hydrolysis of cephalosporin C.